Role of surgery in management of liver abscess - Joshi, Pravin Joshi (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Liver abscess is a common disease in developing world. Its treatment has evolved in last few years to become less and less invasive. Percutaneous drainage of liver abscess is a wellestablished method and probably most widely accepted as well. However, large and multiloculated abscess containing thick pus may not be suitable for such methods. Methods: All patients with liver abscess, who could not be drained or not found suitable for percutaneous drain insertion and eventually underwent surgery were included in the study. Results: Total 8 patients were treated by surgical drainage, open or laparoscopic technique. Surgical drainage was effective way of treatment for abscesses not treatable by needle aspiration or percutaneous tube drain insertion with good outcome. Conclusion: In patient of liver abscess who has large multiloculated abscess with thick pus or not suitable for percutaneous drainage, surgical treatment either laparoscopic or open can be an effective and successful. Journal of Society of Surgeons of Nepal, 2015; 18 (2), page: 20-22